The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.22435/bpk.v47i4.2074
|View full text |Cite
|
Sign up to set email alerts
|

Studi Bioekologi Vektor Malaria di Daerah (Yang Mendapat Sertifikat) Eliminasi Malaria di Kabupaten Jembrana, Bengkalis dan Bulukumba

Abstract: Abstract The target of malaria elimination in Indonesia is expected to be achieved in 2030. One of the activities to support malaria elimination is vector surveillance. Several districts in Indonesia have certificates of malaria, including Jembrana, Bali Province, Bulukumba, South Sulawesi Province, and Bengkalis, Riau Province. Analysis of the presence of malaria vectors and Plasmodium needs to be done for the potential occurances of malaria transmission in eliminated malaria areas. Bioecology study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
2
Order By: Relevance
“…In general mosquitoes found in Central Java sucking blood animal compared to human blood. Species mosquitoes are scattered in the ecosystem forests near and far settlements [19,20]. The breeding habitat of these species vary from fresh water to brackish water.…”
Section: The Biodiversity Of Anopheles As Malaria Vector In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…In general mosquitoes found in Central Java sucking blood animal compared to human blood. Species mosquitoes are scattered in the ecosystem forests near and far settlements [19,20]. The breeding habitat of these species vary from fresh water to brackish water.…”
Section: The Biodiversity Of Anopheles As Malaria Vector In Indonesiamentioning
confidence: 99%
“…A number of Anopheles spp. mosquito breeding sites were discovered in ponds near rivers and springs [20][21][22][23][24][25][26][27]. There is colleration betweeen breeding habitat with the abiotics factor in the environment A study showed that habitats with An.…”
Section: The Biodiversity Of Anopheles As Malaria Vector In Indonesiamentioning
confidence: 99%
“…dalam penelitiannya dengan menyatakan bahwa potensi penularan kembali dapat terjadi karena di wilayah tersebut masih ada Anopheles spp. yang berpotensi sebagai vektor dan kemungkinan adanya malaria impor yang tidak segera ditangani yang kemudian akan berkembang menjadi malaria indigenous, 22 bahkan bisa berkembang menjadi kejadian luar biasa. Oleh karena itu, keberadaan habitat perkembangbiakan larva Anopheles spp.…”
Section: Kesimpulanunclassified
“…There are efforts to implement malaria elimination through applications that empower the community. Malaria elimination activities through various programs malaria elimination activities that have been established through the Global Malaria Program, diagnosis and treatment through the provision of malaria diagnosis guidelines, malaria surveillance activities, Flying Health Care, health development and implementation of malaria control in the community (Yuliyanti, 2016); (Rahayu et al, 2019); (Setiyaningsih, 2020); (Desita et al, 2021a), (Mahdalena & Wurisastuti, 2021); (Ramadhani et al, 2021); (Lenny Gannika, 2019); (Eliza Zihni Zatihulwani, 2019); (Pamuji et al, 2018); (Margaretha Pati Kaka, 2021); (Astuti et al, 2019); (Suryapranata et al, 2022). Prevention efforts in malaria elimination activities are with diagnostic and treatment programs, malaria vaccine, education and research, prevention efforts using the E-SISMAL application, early detection of patients, prevention efforts with vector surveillance activities, prevention efforts with laboratory service approaches and improvements, prevention efforts by evaluating the implementation of the Malaria program, prevention efforts using observation and survey approach with geographic information systems (GIS) (Sesanti & Hastuty, 2021); (NURAINI et al, 2021); (Egbewande, 2022); (Olugbenga et al, 2022); (Moon et al, 2021); (Mahittikorn et al, 2022).…”
Section: Types Of Malaria Elimination Activitiesmentioning
confidence: 99%